Energy-Aware, Self-Contained Nodes for Distributed, Interoperable, and Cross-Domain Internet of Things - Gupta, Amit (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
Numerous vertical platforms are emerging as the backbone of the Internet of Things; these platforms are tailored to a particular use case and typically adopt their own communications, device, and resource management protocols. A unified and secure sharing and access to sensing/actuating resources is made possible via interoperability across IoT platforms, which is becoming more important as the need for cross-domain IoT applications and services grows. This position paper discusses where the Internet of Things (IoT) is at the moment, what potential exist for its sustainable expansion, and what obstacles must be overcome. The goals and vision of the H2020 symbIoTe project are outlined in this context; symbIoTe seeks to facilitate interoperability between IoT platforms by providing a malleable interoperability framework that permits i) cooperation between vertical IoT platforms, ii) the formation of IoT-platform federations for resource sharing, and iii) the development of innovative cross-domain applications by independent developers.